0
$\begingroup$

The solution of the differential equation $\frac{dy}{dx}-xtan(y-x)=1$ will be?

For solving such problems first we should see if the equation is in variable seperable form or not. Obviously here it is not. So I tried to see if it can be made to variable seperable by substitution, but substituting $y-x=z$ would not give the answer as there is one $x$ remaining outside that $tan(y-x)$. Also it is not a homogenous nor is getting converted into homogenous form so that I could substitute $y=vx$ or $x=vy$. So which method should I use here? I am getting wrong answer everytime, please help in dealing with this. Atleast provide me a hint.

$\endgroup$
  • 1
    $\begingroup$ Hint: Try letting $v = y-x$. $\endgroup$ – Moo Mar 27 '17 at 4:25
  • $\begingroup$ I have tried that, but the variable x in multiplication with the tan function gives me the problem. I have mentioned it in my question. $\endgroup$ – Avi Mar 27 '17 at 4:27
  • 1
    $\begingroup$ You get a Separable equation as $\displaystyle \int \cot v ~.dv = \int x ~dx$. What is the problem with that? $\endgroup$ – Moo Mar 27 '17 at 4:29
  • $\begingroup$ OH!! I am really, really sorry for such a silly question. I was not solving it but was just predicting the answer by looking at it. I got it when i took pen in my hand. $\endgroup$ – Avi Mar 27 '17 at 4:33
0
$\begingroup$

Your decision to substitute $z=y-x$ is a good one.

Differentiating with respect to $x$ gives: $$\frac{dz}{dx}=1\cdot \frac{dy}{dx}-1$$ Therefore, rearranging gives: $$\frac{dy}{dx}=\frac{dz}{dx}+1$$ Substituting gives a separable ODE: $$\frac{dz}{dx}+1-x\tan{z}=1$$ $$\frac{dz}{dx}=x\tan{z}$$ Can you continue?

$\endgroup$
0
$\begingroup$

Substituting $y-x=z$ will give the solution.

let $y-x=z$ then $\dfrac{dy}{dx}=1+\dfrac{dz}{dx}$

Now, \begin{align*} \dfrac{dy}{dx}-x\cdot\tan(y-x)&=1\\ \Rightarrow1+\dfrac{dz}{dx}-x\cdot\tan z&=1\\ \Rightarrow\dfrac{dz}{dx}&=x\cdot\tan z\\ \displaystyle\int\cot z\ dz&=\displaystyle\int x\ dx+k\\ \Rightarrow\ln{\left|\sin{z}\right|}&=\dfrac{1}{2}x^2+k\\ \Rightarrow\ln{\left|\sin{z}\right|}^2&=x^2+2k\\ \Rightarrow\sin^2{(y-x)}&=e^{x^2+2k}\\ \Rightarrow\sin^2{(y-x)}&=c\cdot e^{x^2} \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.